(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Violence against women is considered as a global problem and the trend for abusing domestically is very much up. This not only violates the human rights and it has got major implications on physical, mental, social and sexual health of a woman. Worldwide there is little research work on how domestic violence has affected women’s health and their decision-making power. This study aimed to explore the relationship between domestic violence on empowerment of women and their health seeking behavior in Pakistan. Methods: This research has used secondary data from Pakistan Demographic and Health Survey data 2012-13. About 3687 ever-married women were selected and interviewed for domestic violence from 248 urban and 252 rural areas of Pakistan. Results: Both chi-square and binary logistic regression analyses were performed. The results show that women with no education have suffered more (43%) from domestic violence. Almost 68% women reported that who have seen their parents beating their mothers have also experiences domestic violence. Logistic regression shown that women from rural areas are highly likely to be victims of domestic violence (OR=1.28, 95% CI 1.07-1.52, p-value<. 001). ANC visit is also found statistically significant with those who suffered violence at home. Conclusion: Policy makers and other stakeholders should take measures to control and stop violence against women and help them to live equally like a man